EFEKTIVITAS FUNGSI BALAI DIKLAT KEMENTERIAN AGAMA SULAWESI SELATAN TERHADAP KUALITAS GURU PAI DI KOTA MAKASSAR - Asrijal, Asrijal (Jurnal Biotek, 2015)
This study aimstoknow thequality ofthe teachersat the Islamic Religious Educationof Religious Ministry, namelyteaching experience, ability topreparethe lesson plans, learningimplementation, andevaluation.The type of this researchwas akind ofdeskiptive research,in terms ofthe method.The population of this research wasall teacherswhohave been trainedat theTraining Centre ofthe Religious Ministryof Makassar2005-2010. The total of samples which taken in this research were 53from the total of the participants. Because themembersof the population spread to many school, the samplingtechniqueused wasincidental,if it is deemedsuitable asa data sourceforthe teacher whojoined thetrainingfrom various school.The determination ofsuch asampling techniquebased on the consideration, the samplewhich expectedas theunit ofanalysis in this researchwerethe teacherswhospreadevenly inmany schoolsat Makassar.The results showedthat therespondentsobtainedthe highest scorewas 131andthe lowest scorewas29.The mean scorewas72.45; The medianwas73.00; modewas78.00; standarddeviation was23.70. Theresultsgenerally are onaverage category.